Potensi Serat Alam Tanaman Indonesia Sebagai Bahan Fiber Reinforced Composite Kedokteran Gigi - Murdiyanto, Dendy (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Indonesia is a country in tropic area so there are many variatif natural materials. The potency of natural material is a plant which produce fiber for textile industry. The raw textile material in Indonesia are cotton, kapok, rami, rosella, banana and pineapple. Dental treatment use fiber for fiber reinforced composite (FRC) to make denture, dental splinting, post, restoration and retainer. Fiber dental material is a synthetic material imported from other country, some of them doesn’t environment friendly. Many country concern of go green program to save the earth. Fiber reseach must do to find composition,strength, and suitable for dental appliance. Study for the new fiber will done in order to make cheap fiber, last longer and biodegradable material.